2022
DOI: 10.26434/chemrxiv-2022-48jd1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbubble Enhanced Bitumen Separation from Tailing Slurries with High Solid Contents

Abstract: Removing bitumen from oil-sands tailings reduces greenhouse gas emission during waste disposal. However, it is technically challenging to efficiently recover bitumen residual in tailing slurries with high solid contents, due to the tiny fraction of bitumen and complicated composition in the tailings. This work focuses on microbubble-enhanced bitumen recovery in a flow of artificial tailings that consisted of 50 wt% solids, 0.2 wt% bitumen and 49.8 wt% process water. Using a laboratory\textendash scale transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Recently Motamed Dashliborun et al [22] reported experimental work that the optimal bitumen recovery of 50 % was achieved from the oil sand tailings of 6.68 wt % sands and 0.2 wt % bitumen with microbubble injection in a hydrotransport pipeline [22]. Furthermore, a higher bitumen recovery of 70 % from highly concentrated oil sand tailings of 50 wt % sands was obtained in the following work conducted by Zhou et al [23]. Numerous investigations have studied the mechanism of flotation behavior in the presence of microbubbles [25][26][27].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently Motamed Dashliborun et al [22] reported experimental work that the optimal bitumen recovery of 50 % was achieved from the oil sand tailings of 6.68 wt % sands and 0.2 wt % bitumen with microbubble injection in a hydrotransport pipeline [22]. Furthermore, a higher bitumen recovery of 70 % from highly concentrated oil sand tailings of 50 wt % sands was obtained in the following work conducted by Zhou et al [23]. Numerous investigations have studied the mechanism of flotation behavior in the presence of microbubbles [25][26][27].…”
Section: Introductionmentioning
confidence: 92%
“…To recover residual bitumen before discharging to the tailing ponds, several innovative experimental studies have been conducted to enhance bitumen recovery with microbubble injection in a lab-scale pipeline [21][22][23][24]. Though a vast number of theoretical and experimental studies on liquid-solid flow can be found in the literature, very few studies related to the gas-liquid-solid flow were available, and uncertainties exist in modeling this flow.…”
Section: Introductionmentioning
confidence: 99%